Answer: Solution:
and
.
Step-by-step explanation:
The given pair of equations:
![a-8b= -9\ ...(i)\\\\ a-2b= -7\ ...(ii)](https://tex.z-dn.net/?f=a-8b%3D%20-9%5C%20...%28i%29%5C%5C%5C%5C%20a-2b%3D%20-7%5C%20...%28ii%29)
Eliminate equation (i) from (ii) , we get
![-2b-(-8b)=-7-(-9)\\\\\Rightarrow\ -2b+8b=-7+9\\\\\Rightarrow\ 6b=2\\\\\Rightarrow\ b=\dfrac{1}{3}](https://tex.z-dn.net/?f=-2b-%28-8b%29%3D-7-%28-9%29%5C%5C%5C%5C%5CRightarrow%5C%20-2b%2B8b%3D-7%2B9%5C%5C%5C%5C%5CRightarrow%5C%206b%3D2%5C%5C%5C%5C%5CRightarrow%5C%20b%3D%5Cdfrac%7B1%7D%7B3%7D)
Put value of b in (ii) , we get
![a-2\times\dfrac{1}{3}=-7\\\\\Rightarrow\ a=-7+\dfrac{2}{3}\\\\\Rightarrow\ a=\dfrac{-21+2}{3}\\\\\Rightarrow\ a=\dfrac{-19}{3}](https://tex.z-dn.net/?f=a-2%5Ctimes%5Cdfrac%7B1%7D%7B3%7D%3D-7%5C%5C%5C%5C%5CRightarrow%5C%20a%3D-7%2B%5Cdfrac%7B2%7D%7B3%7D%5C%5C%5C%5C%5CRightarrow%5C%20a%3D%5Cdfrac%7B-21%2B2%7D%7B3%7D%5C%5C%5C%5C%5CRightarrow%5C%20a%3D%5Cdfrac%7B-19%7D%7B3%7D)
Solution:
and
.
![$c=\frac{1}{3}](https://tex.z-dn.net/?f=%24c%3D%5Cfrac%7B1%7D%7B3%7D)
Solution:
Given equation is
.
To solve the equation by step by step.
Step 1: Given
![$\frac{8}{3}=3c+\frac{5}{3}$](https://tex.z-dn.net/?f=%24%5Cfrac%7B8%7D%7B3%7D%3D3c%2B%5Cfrac%7B5%7D%7B3%7D%24)
Step 2: Combine like terms together.
Plus symbol changed to minus when the term goes from right to left (or) left to right of the equal sign.
![$\frac{8}{3}-\frac{5}{3}=3c$](https://tex.z-dn.net/?f=%24%5Cfrac%7B8%7D%7B3%7D-%5Cfrac%7B5%7D%7B3%7D%3D3c%24)
Step 3: Subtract the fractions in the left side.
![$\frac{3}{3}=3c$](https://tex.z-dn.net/?f=%24%5Cfrac%7B3%7D%7B3%7D%3D3c%24)
⇒ ![1=3c$](https://tex.z-dn.net/?f=1%3D3c%24)
Step 4: Divide both side of the equation by 3, we get
![$\frac{1}{3} =\frac{3c}{3}$](https://tex.z-dn.net/?f=%24%5Cfrac%7B1%7D%7B3%7D%20%3D%5Cfrac%7B3c%7D%7B3%7D%24)
![$\frac{1}{3} =c$](https://tex.z-dn.net/?f=%24%5Cfrac%7B1%7D%7B3%7D%20%3Dc%24)
Hence, the answer is
.
<em>Answer:</em>
The inequality that is true is -5 - 3x > 10.
<em>Step-by-step explanation:</em>
if x = -6
we can subtitution x to every inequality, so :
-5 - 3x > 10
-5 - 3(-6) > 10
-5 - (-18) > 10
-5 + 18 > 10
13 > 10 [true]
-3 - 5x < -14
-3 - 5(-6) < -14
-3 - (-30) < -14
-3 + 30 < -14
27 < -14 [false]
2 - x < -3
2 - (-6) < -3
2 + 6 < -3
8 < -3 [false]
So if x=-6, inequality true is -5 - 3x > 10.
<em>If this was helpful, please mark brainliest. Have a beautiful day. </em>
Mary Purchase shares = $80,000
Mary Sells shares = $55,000
Loss she can claim for = $80,000 - $55,000
= $ 25,000